Beyond Public Order: Implementing Social Conflict Management Policy for Resident Brawls in South Jakarta - Yunidar; Khasan Effendy (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Metropolitan governments increasingly face a governance paradox in which institutional systems become highly responsive during episodes of urban violence while remaining comparatively fragile in preventing conflict recurrence over the long term. This study examines the implementation of social conflict management policy in handling recurring resident brawls in South Jakarta, Indonesia, with particular attention to the institutional asymmetry between crisis-response governance and preventive governance. Using a qualitative case study approach, the research involved semi-structured interviews, field observation, and document analysis conducted between October 2025 and January 2026. Participants included governmental actors, territorial administrators, security personnel, community representatives, and residents directly associated with conflict-management practices in conflict-prone urban areas. Data were analyzed thematically through an iterative interpretive process focusing on communication, resources, implementer disposition, and bureaucratic structure within policy implementation. The findings reveal that the conflict-management apparatus demonstrated strong operational capacity during escalation and short-term stabilization but lacked equally institutionalized mechanisms for sustained prevention. Communication systems, inter-agency coordination, and emergency response structures functioned effectively during visible crises, whereas preventive intervention remained fragmented, episodic, and highly dependent on localized initiative. Resource limitations, weak predictive governance systems, fragmented preventive responsibility, and crisis-oriented administrative routines collectively reinforced a reactive governance pattern in which institutional response capacity evolved more rapidly than preventive capacity. This study conceptualizes these dynamics as a reactive governance cycle, a condition in which repeated stabilization efforts unintentionally reproduce recurring conflict because long-term vulnerability remains insufficiently addressed. Theoretically, the study contributes to governance and policy-implementation scholarship by explaining how asymmetrical institutional development can sustain recurring urban violence despite the existence of formal policy frameworks and coordinated response systems. Practically, the findings highlight the importance of strengthening preventive institutionalization, predictive governance infrastructure, evidence-based early-warning systems, and integrated cross-sector intervention within metropolitan conflict management.